Foreign Workers in Israel. How Ethno-Nationalism prevents Structures of Representation - Averbukh, Lidia (Momentum Quarterly, 2016)
The main principle the Israeli state relies upon when dealing with documented and undocumented foreign workers is non-involvement. This course of action reflects the restrictive character of Israeli migration regime toward non-Jews. In the first place, the aim is to prevent permanent settlement of foreign workers and therefore, their gradual recognition as residents of Israel. Within the framework of Israeli ethno-nationalism and its immanent dynamic of segregation, foreign workers constitute one isolated group among others. So far the labor migration regime is following ethno-national rules, the labor market can be regularly supplied with workers without challenging the Jewish character of the state. One can observe that recent dynamics in recruitment, such as Asianization, feminization as well as non-recruitment from Arab countries, are not posing a threat to ethno-nationalism but rather consolidate it.